Magnetic images of pharmaceutical dosage forms in the human gastrointestinal tract - Baffa, O.; Corá, L. A. [UNESP]; Américo, M. F.; Fonseca, P. R. [UNESP]; Oliveira, R. B.; Miranda, J. R A [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2005)
Oral administration with solid dosage forms is a common route in the drug therapy widely used. The drug release by the disintegration process occurs in several gastrointestinal tract (GIT) regions. AC Biosusceptometry (ACB) was originally proposal to characterize the disintegration process of tablets in vitro and in the human stomach, through changes in magnetic signals. The aim of this work was to employ a multisensor ACB system to monitoring magnetic tablets and capsules in the human GIT and to obtain the magnetic images of the disintegration process. The ACB showed accuracy to quantify the gastric residence time, the intestinal transit time and the magnetic images allowed to visualize the disintegration of magnetic formulations in the GIT. The ACB is a non-invasive, radiation free technique, completely safe and harmless to the volunteers and had demonstrated potential to evaluate pharmaceutical dosage forms in the human gastrointestinal tract. © 2005 IEEE.
Keywords: AC Biosusceptometry; Disintegration; Gastrointestinal tract; Magnetic images; Biomedical engineering; Decomposition; Gastroenterology; Medical imaging; Sensor data fusion; AC Biosusceptometry (ACB); Gastrointestinal tract (GIT) regions; Magnetic tablets; Drug dosage